Safety in the application of high-velocity low-amplitude technique in upper cervical in elderly: Preliminary study: HVLA in upper cervical of elderly - Zago, Julio; Xavier, Ana Paula; Rondinel, Tatiana; Queiroz, Rogério; Nascimento, Leonardo; Chiappa, Gaspar; Amatuzzi, Fellipe (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: The literature is still controversial regarding the safety of applying high-velocity, low-amplitude (HVLA) techniques to the upper cervical spine, as well as the effects on heart rate variability (HRV) in the elderly. To date, there are no studies reporting the safety of applying these techniques to elderly. Objective: To verify the safety and immediate effects on HRV after applying an HVLA technique to elderly, for the purpose of conducting a future clinical trial. Materials and Methods: This is a preliminary, randomized, crossover study. Six physically active elderly individuals without cardiovascular disease were recruited. The subjects underwent two interventions, with a seven-day interval between them: intervention one consisted of an HVLA technique to the upper cervical spine, while intervention two was a simulated (sham) technique. Data on self-reported symptoms after applying the techniques were collected, in addition to HRV, to assess autonomic function. Results: There were no records of immediate adverse effects after applying the intervention techniques. However, a significant increase in the root means square difference between adjacent normal RR intervals over a time interval (RMSSD) and in the instantaneous beat-to-beat heart rate recording (SD1) was observed in the HVLA group when compared to the sham group. Conclusion: The application of the HVLA technique in the upper cervical spine did not produce self-reported adverse effects in elderly. The HVLA technique increased the activity of the parasympathetic nervous system, producing adjustments in HRV, thus indicating that there may be a significant parasympathetic stimulation in elderly.